CSR STRATEGY: IFAS AND EFAS ANALYSIS OF BATU LUMBANG MANGROVE ECOTOURISM PROGRAM IN NGURAH RAI GRAND FOREST PARK - Choirotunnisa, Maisaroh; Utami, Anita Vijayaningtyas; Akhmad, Dhanar Syahrizal (Progress In Social Development, 2025)
Batu Lumbang Mangrove Ecotourism Program is a corporate social responsibility (CSR) program in empowering fishermen households, developed by PLN Indonesia Power UBP Bali Company. This program was carried out in line with the condition of the Ngurah Rai Grand Forest Park as mangrove conservation area covering an area of 1,373.5 hectares on the South Coast of Denpasar City which faced the problem of potential damage due to waste with a quantity of up to 1.9 tons of garbage in the waste collection event in 2019. This study aims to examine the development strategy of Batu Lumbang Mangrove Ecotourism in Pemogan village, South Coast of Denpasar City. The study method using descriptive qualitative research conducted to analyze program development strategies concerning SWOT (strengths, Weaknesses, Opportunities, and Threats) analysis with Internal Factors Analysis (IFAS) and External Factors Analysis (EFAS) approaches. The results showed that the strengths possessed in the development of Batu Lumbang mangrove ecotourism lie in the strategy of aligning conservation activities and ecosystem utilization. Meanwhile, challenges were found in the form of waste management and infrastructure. The development of community-based mangrove ecotourism can be an effective sustainable development model, by combining environmental conservation, local economic improvement, and community education.